Adeno-Associated Viral Vector-Mediated mTOR Inhibition by Short Hairpin RNA Suppresses Laser-Induced Choroidal Neovascularization - Tae Kwann Park; Si Hyung Lee; Jun Sub Choi; Seung Kwan Nah; Hee Jong Kim; Ha Yan Park; Heuiran Lee; Steven Hyun Seung Lee; Keerang Park (Elsevier, 2017)
Choroidal neovascularization (CNV) is the defining characteristic feature of the wet subtype of age-related macular degeneration (AMD) and may result in irreversible blindness. Based on anti-vascular endothelial growth factor (anti-VEGF), the current therapeutic approaches to CNV are fraught with difficulties, and mammalian target of rapamycin (mTOR) has recently been proposed as a possible therapeutic target, although few studies have been conducted. Here, we show that a recombinant adeno-associated virus-delivered mTOR-inhibiting short hairpin RNA (rAAV-mTOR shRNA), which blocks the activity of both mTOR complex 1 and 2, represents a promising therapeutic approach for the treatment of CNV. Eight-week-old male C57/B6 mice were treated with the short hairpin RNA (shRNA) after generating CNV lesions in the eyes via laser photocoagulation. The recombinant adeno-associated virus (rAAV) delivery vehicle was able to effectively transduce cells in the inner retina, and significantly fewer inflammatory cells and less extensive CNV were observed in the animals treated with rAAV-mTOR shRNA when compared with control- and rAAV-scrambled shRNA-treated groups. Presumably related to the reduction of CNV, increased autophagy was detected in CNV lesions treated with rAAV-mTOR shRNA, whereas significantly fewer apoptotic cells detected in the outer nuclear layer around the CNV indicate that mTOR inhibition may also have neuroprotective effects. Taken together, these results demonstrate the therapeutic potential of mTOR inhibition, resulting from rAAV-mTOR shRNA activity, in the treatment of AMD-related CNV. Keywords: retinal neovascularization, choroidal neovascularization, adeno-associated virus, mTOR, RNA interference, mTOR shRNA, autophagy